Ideological Representation and Gender Bias in Indonesian Language Textbooks - Selpina Tekege (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study examines ideological representation and gender bias in Indonesian language textbooks through a systematic literature review. It aims to identify how textbooks construct ideological meanings and gender roles within Indonesian language education. Using the PRISMA framework, articles were collected from Google Scholar, resulting in 179 records, of which 23 studies met the eligibility criteria and were included in the final analysis. The findings show that Indonesian language textbooks function not only as instructional materials but also as ideological sites that shape identity, morality, authority, nationalism, and gender relations. Gender bias appears not only in unequal male and female visibility, but also in textual choices, visual representations, role distribution, and symbolic positioning that tend to privilege male authority and public agency. The novelty of this study lies in integrating ideological representation and gender bias within a single analytical framework. This study contributes to the literature by offering a more comprehensive understanding of textbook discourse and by providing a basis for developing more inclusive and gender-responsive Indonesian language textbooks.